TIGAR inhibits glucose-metabolism and cisplatin-chemosensitivity in human lung cancer cells - Yang Feng; Yiling Meng; Meichao Zhang; Yingxia Ying; Yuan Yao; Dong Li (Discover Oncology)
Abstract TIGAR is an important factor associated with tumor glucose metabolism, but its function and underlying mechanism in human lung cancer remains unclear. Here, we analyzed the expression changes, prognosis, genetic alteration, related gene networks and metabolic pathways of TIGAR in lung cancer. The findings revealed that TIAGR level was augmented in LUAD and LUSC in comparison to the normal lung tissue. In addition, high TIAGR level was related to poorer outcome of patients with LUAD. Different alterations in TIGAR gene at various sites were observed in both LUAD and LUSC. The GO/KEGG analyses indicated that TIGAR affects the occurrence and progress of lung cancer through multiple metabolic pathways. Further, we established lung cancer cell models with TIGAR knockdown or overexpression to explore its effects on glucose metabolism, apoptosis and chemosensitivity. Our results indicated that TIGAR markedly inhibited glucose metabolism, ROS production, and susceptibility of lung cancer cells to cisplatin. Together, TIGAR plays a cancer-promoting role in lung cancer, which becomes a promising prognostic and therapeutic biomarker.